Laminate and packaging material
The laminate structure with a high melting point resin surface layer, high-density intermediate layer, and polyethylene back layer addresses the challenges of recyclability and heat resistance in packaging materials, ensuring effective gas barrier properties post-sterilization.
Patent Information
- Application Number
- JP2023094717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional laminates used for packaging materials face challenges in achieving high recyclability, good heat sealability, and maintaining gas barrier properties after heat sterilization, which are essential for monomaterialization and environmental sustainability.
A laminate structure comprising a base film with specific layers, including a surface layer with a higher melting point resin, an intermediate layer with high-density polyethylene resin, and a back layer with medium or high-density polyethylene resin, designed to maintain gas barrier properties and heat resistance, with a polyethylene resin content of 90% or more.
The laminate provides excellent recyclability, heat sealability, and heat resistance, ensuring effective gas barrier properties even after heat sterilization, thereby enhancing processing stability and efficiency.
Smart Images

Figure 2024176275000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a packaging material. [Background technology]
[0002] Packaging materials used for packaging foods, medicines, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents (gas barrier properties) in order to prevent deterioration and spoilage of the contents and to maintain their function and quality. In addition, packaging materials are required to have excellent heat resistance because they may be subjected to heat sterilization treatment such as boiling. For this reason, laminates having gas barrier properties and heat resistance are used for these packaging materials.
[0003] As such laminates, for example, Patent Documents 1 to 3 disclose laminates in which a gas barrier layer such as a metal foil or a metal vapor deposition film is provided on the surface of a resin substrate such as a polyethylene film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-55157 A [Patent Document 2] JP 2001-179878 A [Patent Document 3] JP 2018-024213 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, due to growing environmental awareness triggered by the problem of marine plastic waste, there is a demand for more efficient sorting and recovery of plastic materials and recycling, and there is also a demand for mono-material packaging materials.
[0006] However, as the inventors conducted studies in proceeding with the development of a mono-material, they found that there was room for improvement in conventional laminates in terms of their heat sealability, i.e., the ability to heat seal without melting or deforming the base layer, and their heat resistance, i.e., the processing stability when providing a gas barrier layer, and the ability to maintain gas barrier properties even after heat sterilization treatment.
[0007] The present invention has been made in view of the above circumstances, and has an object to provide a laminate having excellent recyclability, good heat sealability and heat resistance, and a packaging material including the laminate. [Means for solving the problem]
[0008] The present invention relates to, for example, the following [1] to [9]. [1] A laminate comprising a base film, an inorganic oxide layer, an adhesive layer, and a sealant layer in this order, the base film has a surface layer, an intermediate layer, and a back layer on a sealant layer side in this order; The surface layer contains a resin having a higher melting point than polyethylene resin, the intermediate layer contains polyethylene resin, and the back layer has a melting point of 0.926 g / cm 3 The polyethylene resin has a density of at least the probe drop temperature of the back layer is 130° C. or more and less than 150° C., and the probe drop temperature of the intermediate layer is higher than the probe drop temperature of the back layer; the sealant layer comprises a polyethylene resin; A laminate, wherein the content of the polyethylene resin in the laminate is 90 mass% or more based on the total amount of the laminate. [2] The laminate according to [1], wherein the thickness of the surface layer is 0.3 μm or more and 6 μm or less. [3] The laminate according to [1] or [2], wherein the intermediate layer has a probe drop temperature of 140° C. or higher. [4] The laminate according to any one of [1] to [3], wherein the thickness of the intermediate layer is 33% or more of the thickness of the base film. [5] The laminate according to any one of [1] to [4], wherein the base film is a non-stretched film. [6] The laminate according to any one of [1] to [5], further comprising a gas barrier coating layer on a surface of the inorganic oxide layer on the sealant layer side. [7] The laminate according to any one of [1] to [6], wherein the adhesive layer contains a gas barrier adhesive. [8] The laminate according to any one of [1] to [7], wherein a difference (T1-T2) between a heat seal initiation temperature T1 when the surface layers are placed opposite each other and heat sealed, and a heat seal initiation temperature T2 when the sealant layers are placed opposite each other and heat sealed, is 40°C or more. <Method for measuring heat seal start temperature> The surface layers or sealant layers of the laminate are sandwiched between PET films with each layer facing each other, and heat sealed using a heat sealer under the following conditions: sealing pressure 0.2 MPa, sealing time 1 second, and seal width 10 mm. The sealing temperature is adjusted in 10°C increments between 90 and 240°C. The heat-sealed portions heat-sealed at each temperature are cut into 15 mm widths, T-peeled at a tensile speed of 300 m / min, and the heat-seal strength of the heat-sealed portions is measured. The temperature at which the heat-seal strength reaches 2 N / 15 mm or more is taken as the heat-seal rise temperature. [9] A packaging material comprising the laminate according to any one of [1] to [8]. Effect of the Invention
[0009] According to the present invention, there is provided a laminate having excellent recyclability, good heat sealability and good heat resistance. Also, according to the present invention, there is provided a packaging material including the laminate. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view of a laminate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a laminate according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a laminate according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Note that the drawings are schematic, and for example, the relationship between thickness and planar dimensions, and the ratio of thicknesses of each layer are different from the actual ones. In addition, the embodiments shown below are examples of configurations for embodying the technical idea of the present disclosure, and the technical idea of the present disclosure is not limited to the materials, shapes, structures, etc. of the components described below.
[0012] [Laminate] 1 is a cross-sectional view of a laminate according to one embodiment of the present invention. The laminate 100 includes a substrate film 10, a gas barrier layer 20 (an inorganic oxide layer 21 and a gas barrier coating layer 22), an adhesive layer 30, and a sealant layer 40.
[0013] The content of the polyethylene resin in the laminate 100 is 90% by mass or more, based on the total amount of the laminate 100, from the viewpoint of realizing mono-materialization and excellent recyclability, but may be 95% by mass or more.
[0014] The thickness of the laminate 100 is not particularly limited and can be appropriately determined depending on the cost and the application. The thickness of the laminate 100 may be 50 μm or more, 60 μm or more, or 70 μm or more, and may be 300 μm or less, 250 μm or less, or 200 μm or less.
[0015] In the laminate 100, the difference (T1-T2) between the heat seal start temperature T1 when heat sealing is performed with the surface layers facing each other and the heat seal start temperature T2 when heat sealing is performed with the sealant layers facing each other is preferably 40°C or more, more preferably 50°C or more. This ensures good heat sealability and allows for a wider range of heat seal temperature conditions during bag making, improving bag making efficiency. There is no particular upper limit to the difference, but it can be 150°C or less. The heat seal rise temperature is a temperature measured as follows. The heat seal rise temperature can also be called the heat seal strength rise temperature, the heat seal welding temperature, the heat seal curve rise temperature, or the like.
[0016] (Method for measuring heat seal rise temperature) The surface layers or sealant layers of the laminate are sandwiched between PET films with each layer facing each other, and heat sealed using a heat sealer under the following conditions: sealing pressure 0.2 MPa, sealing time 1 second, and seal width 10 mm. The sealing temperature is adjusted in 10°C increments between 90 and 240°C. The heat-sealed portions heat-sealed at each temperature are cut into 15 mm widths, T-peeled at a tensile speed of 300 m / min, and the heat-seal strength of the heat-sealed portions is measured. The temperature at which the heat-seal strength reaches 2 N / 15 mm or more is taken as the heat-seal rise temperature.
[0017] <Base film> The base film 10 has three layers, in this order: a surface layer 11, an intermediate layer 12, and a back layer 13 on the sealant layer side. The surface layer 11 and the back layer 13 are each the outermost layers of the base film 10. The base film 10 is a multilayer film that can be obtained by coextrusion, and therefore can also be called a coextruded multilayer film.
[0018] The content of the polyethylene resin in the base film 10 may be 90% by mass or more, or 95% by mass or more, based on the total amount of the base film 10, from the viewpoint of realizing mono-materialization and excellent recyclability.
[0019] The base film 10 may be a non-stretched film. When the base film 10 is non-stretched, the gas barrier layer 20 is less likely to peel off near the surface of the base film 10, and the adhesion to the gas barrier layer 20 is excellent.
[0020] The thickness of the base film 10 is not particularly limited and can be appropriately determined according to the cost and application while taking into consideration the suitability as a packaging material and the suitability for lamination with other layers. The thickness of the base film 10 may be 3 μm or more, 5 μm or more, 6 μm or more, or 10 μm or more, or may be 200 μm or less, 120 μm or less, 100 μm or less, or 40 μm or less.
[0021] (surface) The surface layer 11 contains a resin having a higher melting point than polyethylene resin (hereinafter referred to as high melting point resin). The surface layer 11 has a function of preventing defects during heat sealing during bag making or filling and sealing, such as adhesion of base film components to a heat seal bar and deformation of the base film, and ensuring heat sealing suitability. It can also be said that the surface layer 11 contains a resin having a higher melting point than the resin contained in the intermediate layer 12.
[0022] Examples of high melting point resins include homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, olefin resins such as polybutene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, ethylene-vinyl alcohol copolymers, polyamides, etc. These may be used alone or in combination of two or more. Among these, polyamides can be preferably used from the viewpoint of heat sealability and rigidity.
[0023] The melting point of the high melting point resin is not particularly limited, but considering that the melting point of the polyethylene resin of the sealant layer is 95 to 135° C., it may be more than 135° C., 140° C. or more, or 150° C. or more. The upper limit of the melting point of the high melting point resin may be 350° C. from the viewpoint of film formability. The "melting point" of a resin is a value measured based on JIS K 7121.
[0024] The surface layer 11 may contain a resin other than the high melting point resin to the extent that the above-mentioned function of the surface layer 11 is not impaired. Examples of resins other than the high melting point resin include polyethylene resins, specifically the polyethylene resins exemplified in the intermediate layer 12 and the back layer 13. However, from the viewpoint of easily achieving the above-mentioned function of the surface layer 11, the content of the high melting point resin in the surface layer 11 may be 10% by mass or more, 25% by mass or more, or 50% by mass or more based on the total amount of the surface layer 11, or may be 100% by mass (an embodiment in which the surface layer 11 is substantially made of the high melting point resin).
[0025] From the viewpoint of heat sealability and heat resistance, the probe drop temperature of the surface layer 11 may be 155° C. or more, 200° C. or more, 250° C. or more, or 300° C. or more. From the viewpoint of film formability, the probe drop temperature of the surface layer 11 may be 450° C. or less, or 400° C. or less. The probe drop temperature is a value measured by the method described below.
[0026] The probe drop temperature is a parameter related to the local thermal analysis of a material using a probe, and can be obtained by measuring the rising and falling behavior of the probe. To measure the probe drop temperature, an atomic force microscope (AFM) equipped with a cantilever (probe) with a heating mechanism and a nanothermal microscope is used. When the cantilever is brought into contact with the surface of a solid sample fixed to a sample stage and a voltage is applied to the cantilever in contact mode to heat it, the sample surface thermally expands and the cantilever rises. When the cantilever is further heated, the sample surface softens and its hardness changes significantly. As a result, the cantilever descends and penetrates into the sample surface. The starting point of the sudden displacement detected at this time is the probe drop starting point, and the probe drop temperature can be obtained by converting the voltage into temperature. By this method, the probe drop temperature can be known locally in the nanoscale region and near the surface.
[0027] Examples of AFMs that can be used include the MPF-3D-SA and Ztherm systems manufactured by Oxford Instruments, and the Nano Thermal Analysis series and nanoIR series manufactured by Bruker Japan. Measurements can also be performed with AFMs manufactured by other manufacturers by attaching the Nano Thermal Analysis. Examples of cantilevers that can be used include the AN2-200 manufactured by Anasys Instruments. Cantilevers other than those listed above can be used as long as they can sufficiently reflect laser light and can be applied with voltage.
[0028] The temperature range in the measurement of the probe drop temperature varies depending on the material to be measured, but for example, the start temperature can be about room temperature, 25° C., and the end temperature can be about 400° C. The temperature range in the measurement of the probe drop temperature may be from 25° C. to 300° C.
[0029] The spring constant of the cantilever may be 0.1 to 3.5 N / m, and is preferably 0.5 to 3.5 N / m in order to perform measurements in both tapping and contact modes. In AFM, the deflection of the cantilever may be detected in units of voltage. In contact mode, the deflection of the cantilever changes before and after contact between the cantilever and the sample. By keeping this change within the range of 0.1 to 3.0 V, it is possible to prevent damage to the sample surface while keeping the cantilever in contact with the sample.
[0030] The temperature rise rate of the cantilever varies depending on the heating mechanism, etc., but may be 0.1 to 10 V / sec, and is preferably 0.2 to 5 V / sec. When the sample surface softens, the tip of the cantilever penetrates into the sample and descends. The amount of penetration of the cantilever affects the detection sensitivity of the peak top of the softening curve, and can be 3 to 500 nm. From the viewpoint of preventing damage to the cantilever, it is more preferable to set the amount of penetration to 5 to 100 nm.
[0031] In order to calculate the probe drop temperature, it is necessary to create a calibration curve. In the examples described later, polycaprolactone, low-density polyethylene, polypropylene, and polyethylene terephthalate were used as calibration samples to create the calibration curve. The material of the calibration sample is not limited to the above, and at least one of the following may be used: a material whose thermal conductivity is not significantly different from that of a general polymer, and whose melting point is near 60°C, near 250°C, and between them. For example, it is also possible to use only three of the above four calibration samples, excluding polypropylene: polycaprolactone, low-density polyethylene, and polyethylene terephthalate.
[0032] The thickness of the surface layer 11 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. The thickness of the surface layer 11 may be 0.3 μm or more, 0.5 μm or more, or 1 μm or more from the viewpoint of heat resistance (ability to heat seal without problems when heated from the surface layer side), and may be 6 μm or less, 5 μm or less, or 4 μm or less from the viewpoint of recyclability.
[0033] (Middle class) The intermediate layer 12 is a layer containing a polyethylene resin. Hereinafter, the polyethylene resin constituting the intermediate layer 12 is also referred to as a first polyethylene resin. The content of the first polyethylene resin in the intermediate layer 12 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the intermediate layer 12, or may be 100% by mass (an embodiment in which the intermediate layer 12 is substantially composed of the first polyethylene resin). When the intermediate layer 12 is composed of a plurality of polyethylene resins (e.g., a plurality of polyethylene resins having different average molecular weights, densities, etc.), a mixture of the plurality of polyethylene resins is defined as the first polyethylene resin.
[0034] From the viewpoints of preventing wrinkles from occurring when laminating a gas barrier layer and providing better processing stability, and of more easily maintaining gas barrier properties even after heat sterilization treatment and providing better heat resistance, the intermediate layer 12 may be made of a first polyethylene resin having a density in the following range. The density of the first polyethylene resin is 0.942 g / cm 3 More than 0.945g / cm 3 or more than 0.950g / cm 3 The density of the first polyethylene resin may be 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 or less than 0.965g / cm 3 It may be the following. The density of the resin (resin film) is a value measured based on JIS Z 8837.
[0035] The melt flow rate (MFR) of the first polyethylene resin at 190°C under a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the first polyethylene resin. The MFR of the first polyethylene resin may be 5 g / 10 min or less, 3 g / 10 min or less, 2 g / 10 min or less, or 1.5 g / 10 min or less. The MFR of the first polyethylene resin may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, or 0.8 g / 10 min or more. The melt flow rate of a resin (resin film) is a value measured based on JIS K6921-2.
[0036] The higher the probe drop temperature of the intermediate layer 12, the easier it is to achieve excellent heat resistance. The probe drop temperature of the intermediate layer 12 may be 140°C or higher, 142°C or higher, or 150°C or higher from the viewpoints of wrinkles being less likely to occur and excellent processing stability, and of gas barrier properties and adhesion being more easily maintained even after heat sterilization treatment and excellent heat resistance. The probe drop temperature of the intermediate layer 12 may be 170°C or lower, 165°C or lower, 160°C or lower, 157°C or lower, or 155°C or lower.
[0037] The probe descent temperature of the intermediate layer 12 is higher than the probe descent temperature of the back layer 13. This makes it possible to prevent wrinkles from occurring, achieve excellent heat resistance, and maintain gas barrier properties even after heat sterilization.
[0038] The difference between the probe drop temperature of the intermediate layer 12 and the probe drop temperature of the back layer 13 may be 3° C. or more, 5° C. or more, or 8° C. or more, from the viewpoints of preventing wrinkles from occurring more easily when laminating the gas barrier layer and improving processing stability, and of making it easier to maintain gas barrier properties and adhesion even after heat sterilization treatment and improving heat resistance. The difference between the probe drop temperature of the intermediate layer 12 and the probe drop temperature of the back layer 13 may be 25° C. or less, 20° C. or less, 15° C. or less, or 13° C. or less.
[0039] The probe drop temperature of the surface layer 11 is higher than the probe drop temperature of the intermediate layer 12. This improves the heat sealability of the laminate, making it less likely that problems will occur during heat sealing during bag making or filling and sealing.
[0040] From the viewpoint of improving heat sealability, the difference between the probe drop temperature of the surface layer 11 and the probe drop temperature of the intermediate layer 12 may be 10° C. or more, 30° C. or more, or 50° C. or more. The difference between the probe drop temperature of the surface layer 11 and the probe drop temperature of the intermediate layer 12 may be 200° C. or less, 150° C. or less, or 100° C. or less.
[0041] The thickness of the intermediate layer 12 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the intermediate layer 12 may be 5 μm or more, 8 μm or more, 10 μm or more, 12 μm or more, or 15 μm or more, or may be 80 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.
[0042] The thicker the intermediate layer 12, the better the heat resistance that can be achieved. From the viewpoints of preventing wrinkles from occurring, of making it easier to maintain gas barrier properties and adhesion even after heat sterilization, and of achieving better heat resistance, the thickness of the intermediate layer 12 may be 33% or more, 40% or more, 50% or more, 55% or more, or 60% or more of the thickness of the base film 10. The thickness of the intermediate layer 12 may be 90% or less, 85% or less, or 80% or less of the thickness of the base film 10.
[0043] The thickness of the intermediate layer 12 may be greater than the thickness of the surface layer 11 and / or the thickness of the back layer 13, from the viewpoint of more easily maintaining the gas barrier property and adhesion even after heat sterilization treatment and more excellent heat resistance. The thickness of the intermediate layer 12 may be 1 or more times, 1.5 or more times, 2 or more times, or 3 or more times the thickness of the surface layer 11 and / or the back layer 13, from the viewpoint of more easily maintaining the gas barrier property and adhesion even after heat sterilization treatment and more excellent heat resistance. The thickness of the intermediate layer 12 may be 10 or less times, 8 or less times, or 5 or less times the thickness of the surface layer 11 and / or the back layer 13.
[0044] (Back layer) The back layer 13 is a layer containing a polyethylene resin, and may contain a medium density polyethylene resin or a high density polyethylene resin. Hereinafter, the polyethylene resin constituting the back layer 13 is also referred to as a second polyethylene resin. The content of the second polyethylene resin in the back layer 13 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the back layer 13, or may be 100% by mass (an embodiment in which the back layer 13 is substantially composed of the second polyethylene resin). When the back layer 13 is composed of a plurality of polyethylene resins (e.g., a plurality of polyethylene resins having different average molecular weights, densities, etc.), a mixture of the plurality of polyethylene resins is the second polyethylene resin.
[0045] The back layer 13 has a viscosity of 0.926 g / cm from the viewpoints of preventing wrinkles from occurring when laminating a gas barrier layer, improving processing stability, and making it easier to maintain gas barrier properties even after heat sterilization treatment and improving heat resistance.3 The polyethylene resin may be made of a medium density polyethylene resin or a high density polyethylene resin (second polyethylene resin) having a density of at least 1000 nm. The density of the second polyethylene resin is 0.926 g / cm 3 More than 0.930g / cm 3 More than 0.935g / cm 3 or more than 0.940g / cm 3 The density of the second polyethylene resin may be 0.970 g / cm or more. 3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 The density of the second polyethylene resin may be 0.970 g / cm or less. 3 By satisfying the condition below, the surface of the base film 10 can be prevented from becoming rough.
[0046] The probe drop temperature of the back layer 13 is 130° C. or more, but may be 133° C. or more, from the viewpoints of preventing wrinkles from occurring when laminating a gas barrier layer and providing better processing stability, and of making it easier to maintain gas barrier properties even after heat sterilization treatment and providing better heat resistance. The probe drop temperature of the back layer 13 is less than 150° C., but may be 146° C. or less. By having the probe drop temperature of the back layer 13 be less than 150° C., it is possible to prevent the surface of the base film 10 from becoming rough.
[0047] The thickness of the back layer 13 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the back layer 13 may be 0.3 μm or more, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, or may be 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.
[0048] The intermediate layer 12 and the back layer 13 may contain a resin other than polyethylene resin as appropriate, as long as the recyclability is not impaired. Examples of such resins include ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, olefin resins such as polybutene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, ethylene-vinyl alcohol copolymer, polyamide, various modifying resins, and the like. In addition, each layer may independently contain one or more additives. Examples of additives include crosslinking agents, antioxidants, antiblocking agents, lubricants (slip agents), ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments.
[0049] The intermediate layer 12 may be a single layer or may be formed of multiple layers. For example, as shown in Fig. 2, the base film 50 in the laminate 200 has a front layer 51, an intermediate layer 52, and a back layer 53, and the intermediate layer 52 has resin layers 52a, 52b, and 52c. In this case, the resin layers 52a, 52b, and 52c all have the same composition.
[0050] The base film 10 may have layers other than the three layers of the surface layer 11, the intermediate layer 12, and the back layer 13. For example, as shown in FIG. 3, the base film 60 in the laminate 300 has a surface layer 61, an intermediate layer 62, and a back layer 63, a resin layer 64 between the surface layer 61 and the intermediate layer 62, and a resin layer 65 between the intermediate layer 62 and the back layer 63. The resin layer 64 is, for example, a layer containing a polyethylene resin and having a different composition from the surface layer 61 and the intermediate layer 62. The resin layer 65 is, for example, a layer containing a polyethylene resin and having a different composition from the intermediate layer 62 and the back layer 63. The resin layers 64 and 65 have the function of bonding different layers, and therefore can also be called adhesive layers formed from adhesive resins. The substrate film 10 may have, for example, three layers, five layers, seven layers, or more layers.
[0051] The method for producing the base film 10 is not particularly limited, and the base film 10 can be produced by a known co-extrusion method such as an air-cooled inflation method, a water-cooled inflation method, or a T-die casting method. From the viewpoint of versatility, the base film 10 may be produced by an inflation method or an air-cooled inflation method. The air-cooled inflation method is a method in which a die having an annular lip called a ring die (or a crosshead die) is installed at the tip of an extruder, and a material is extruded into a tube shape and continuously molded. More specifically, an air hole is installed in the center of the ring die, and compressed air is blown in from the air hole to expand the tube, and the film is cooled while being pulled by a roller called a pinch roll, and then the film is wound up, whereby the base film 10 can be produced.
[0052] The obtained substrate film 10 may be subjected to a surface modification treatment to improve suitability for subsequent processes, if necessary. For example, the surface of the substrate film 10 may be modified to improve printability or lamination suitability during lamination. Examples of the modification treatment include treatments that generate functional groups by oxidizing the film surface, such as corona discharge treatment, plasma treatment, and frame treatment, and modification treatments by a wet process that forms an easy-adhesion layer by coating.
[0053] <Gas barrier layer> The gas barrier layer 20 is a layer provided on the base film 10 from the viewpoint of improving the gas barrier property against water vapor and oxygen. The gas barrier layer 20 is preferably a layer having transparency. The gas barrier layer 20 has an inorganic oxide layer 21 and a gas barrier coating layer 22. The gas barrier layer 20 may have both the inorganic oxide layer 21 and the gas barrier coating layer 22, or may have only the inorganic oxide layer 21.
[0054] (Inorganic oxide layer) The inorganic oxide layer 21 contains an inorganic oxide. Examples of inorganic oxides include aluminum oxide, silicon oxide, tin oxide, magnesium oxide, and mixtures thereof. From the viewpoint of more easily maintaining gas barrier properties and adhesion even after heat sterilization treatment, more excellent heat resistance, and transparency, the inorganic oxide layer 21 may contain at least one selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide.
[0055] The thickness of the inorganic oxide layer 21 may be 5 to 150 nm. If the thickness of the inorganic oxide layer 21 is 5 nm or more, it is easy to form a layer having a uniform and sufficient film thickness, and sufficient gas barrier properties can be realized. If the thickness of the inorganic oxide layer 21 is 150 nm or less, flexibility can be imparted to the inorganic oxide layer 21, and even if an external load such as bending or pulling is applied after the inorganic oxide layer 21 is formed, the inorganic oxide layer 21 can be prevented from cracking. The thickness of the inorganic oxide layer 21 may be 6 nm or more, or 8 nm or more, or 100 nm or less, or 50 nm or less.
[0056] The inorganic oxide layer 21 can be formed by a normal vacuum deposition method. It can also be formed by other thin film formation methods such as sputtering, ion plating, plasma vapor deposition (CVD), etc. The inorganic oxide layer 21 may be formed by the vacuum deposition method from the viewpoint of excellent productivity.
[0057] The heating means for the vacuum deposition method may be any of the electron beam heating method, the resistance heating method, and the induction heating method. The vacuum deposition method may be the electron beam heating method from the viewpoint of a wide range of evaporation material selection. From the viewpoint of improving the adhesion between the base film 10 and the inorganic oxide layer 21 and the denseness of the inorganic oxide layer 21, deposition may be performed by a plasma assist method, an ion beam assist method, or the like. From the viewpoint of improving the transparency of the inorganic oxide layer 21, deposition may be performed by reactive deposition.
[0058] (Gas barrier coating layer) The gas barrier coating layer 22 is a layer provided for the purpose of protecting the inorganic oxide layer 21 and complementing the gas barrier property. The laminate 100 does not necessarily have to include the gas barrier coating layer 22.
[0059] The gas barrier coating layer 22 may be a heat-cured product of a composition containing at least one of a water-soluble polymer and its hydrolysate, and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and their hydrolysates.
[0060] Examples of the water-soluble polymer include hydroxyl group-containing polymer compounds such as polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. The water-soluble polymer may be polyvinyl alcohol (PVA) from the viewpoint of excellent gas barrier properties.
[0061] Examples of metal alkoxides include compounds represented by the following general formula: M(OR 11 ) m (R 12 ) n-m …(1) In the above formula (1), R 11 and R 12 R is each independently a monovalent organic group having 1 to 8 carbon atoms. 11 and R 12 may each independently be an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 11 and R 12 If there are multiple, R 11 R 12 They may be the same or different.
[0062] Examples of the metal alkoxide include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. The metal alkoxide may be tetraethoxysilane or triisopropoxyaluminum from the viewpoint of being relatively stable in an aqueous solvent after hydrolysis.
[0063] Examples of the silane coupling agent include compounds represented by the following general formula: Si(OR 21 ) p (R 22 ) 3-p R 23 …(2) In the above formula (2), R 21 represents an alkyl group such as a methyl group or an ethyl group, and R 22 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 23 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 21 or R 22 If there are multiple, R 21 R 22 R may be the same or different. 23 Examples of the monovalent organic functional group represented by the formula (I) include monovalent organic functional groups containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, and an isocyanate group.
[0064] Examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and 3-isocyanatealkylalkoxysilane.
[0065] The silane coupling agent may be a polymer such as a dimer or trimer of the above-mentioned silane coupling agent. As the polymer, a trimer is preferable, for example, 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate. This is a condensation polymer of 3-isocyanate alkylalkoxysilane. By adding 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate to a water-soluble polymer, the water resistance of the gas barrier coating layer can be improved by hydrogen bonding.
[0066] The gas barrier coating layer 22 can be formed using a composition (hereinafter referred to as an overcoat agent) obtained by adding a water-soluble polymer and a metal alkoxide and / or a silane coupling agent to water or a water / alcohol mixture. The overcoat agent can be prepared by mixing, for example, a solution in which a hydroxyl-containing polymer compound, which is a water-soluble polymer, is dissolved in an aqueous (water or water / alcohol mixture) solvent with a metal alkoxide and / or a silane coupling agent directly or after being previously treated by hydrolysis or the like. Additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant may be added to the overcoat agent.
[0067] The amount of the metal alkoxide in the overcoat agent can be 1 to 4 parts by mass, or may be 2 to 3 parts by mass, per 1 part by mass of the water-soluble polymer, from the viewpoint of maintaining adhesion to the inorganic oxide layer 21 and gas barrier properties. Similarly, the amount of the silane coupling agent can be 0.01 to 1 part by mass, or may be 0.1 to 0.5 parts by mass, per 1 part by mass of the water-soluble polymer. When a silane compound (alkoxysilane) is used as the metal alkoxide, the amount of the silane compound (metal alkoxide and silane coupling agent) in the overcoat agent can be 1 to 4 parts by mass, or may be 2 to 3 parts by mass, per 1 part by mass of the water-soluble polymer.
[0068] The overcoat agent can be applied onto the inorganic oxide layer 21 by, for example, a dipping method, a roll coating method, a gravure coating method, a reverse gravure coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, a gravure offset method, etc. The coating film obtained by applying the overcoat agent can be dried by, for example, a hot air drying method, a hot roll drying method, a high frequency irradiation method, an infrared irradiation method, a UV irradiation method, or a combination thereof.
[0069] The temperature for drying the coating film may be, for example, 50 to 150° C., and is preferably 70 to 100° C. By keeping the drying temperature within the above range, the occurrence of cracks in the gas barrier layer 20 can be further suppressed, and excellent barrier properties can be exhibited.
[0070] The gas barrier coating layer 22 may be formed using an overcoat agent containing a water-soluble polymer (e.g., polyvinyl alcohol resin) and a silane compound. The overcoat agent may contain an acid catalyst, an alkali catalyst, a photopolymerization initiator, etc., as necessary. Examples of the silane compound include a silane coupling agent, polysilazane, siloxane, etc., and specific examples thereof include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, hexamethyldisilazane, etc.
[0071] The gas barrier coating layer 22 described above can maintain excellent gas barrier properties even after heat sterilization. Therefore, when the laminate 100 is used as a packaging material for heat sterilization, the packaging material has excellent adhesion even after heat sterilization. In addition, the gas barrier coating layer 22 described above is preferable because it has sufficient transparency, bending resistance, and stretch resistance, and there is no risk of generating harmful substances such as dioxins.
[0072] The thickness of the gas barrier coating layer 22 may be 0.05 μm or more, or 0.1 μm or more, from the viewpoint of excellent gas barrier properties. The thickness of the gas barrier coating layer 22 may be 1 μm or less, or 0.5 μm or less, from the viewpoints of easily forming a uniform coated surface, reducing the load due to drying, flexibility, and production costs.
[0073] (Anchor coat layer) From the viewpoint of improving the adhesion between the base film 10 and the gas barrier layer 20, an anchor coat layer (not shown) may be provided between the base film 10 and the gas barrier layer 20. By providing the anchor coat layer, it becomes easier to maintain the gas barrier properties and adhesion even after heat sterilization treatment.
[0074] The anchor coat layer can be formed, for example, from a coating liquid containing a resin such as an acrylic resin, an epoxy resin, an acrylic urethane resin, a polyester polyurethane resin, a polyether polyurethane resin, etc. From the viewpoint of heat resistance and interlayer adhesive strength, the anchor coat layer may be formed from a coating liquid containing an acrylic urethane resin or a polyester polyurethane resin.
[0075] The method for applying the coating liquid for forming the anchor coat layer may be a known coating method, and examples thereof include an immersion method (dipping method), a method using a spray, a coater, a printer, a brush, etc. Examples of the types of coaters and printers used in these methods and the coating methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.
[0076] The method for drying the anchor coat layer is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to a coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Drying conditions can be appropriately selected depending on the drying method, and for example, in a method of drying in an oven, drying may be performed at 60 to 100°C for about 1 second to 2 minutes.
[0077] The thickness of the anchor coat layer may be 0.01 μm or more, 0.03 μm or more, or 0.05 μm or more from the viewpoint of easily obtaining sufficient adhesion between layers. The thickness of the anchor coat layer may be 5 μm or less, 3 μm or less, or 2 μm or less from the viewpoint of excellent gas barrier property.
[0078] <Adhesive layer> The adhesive layer 30 is a layer containing at least one type of adhesive, and is provided between the gas barrier layer 20 and the sealant layer 40 to bond them together. The adhesive layer 30 can be formed using a known adhesive. The adhesive may be, for example, a dry lamination adhesive. The dry lamination adhesive is not particularly limited, and examples thereof include ester adhesives, ether adhesives, and urethane adhesives. These adhesives may be one-component curing types or two-component curing types.
[0079] From the viewpoint of excellent gas barrier properties, the adhesive layer 30 may be formed using a gas barrier adhesive. Even if minute cracks occur in the inorganic oxide layer 21 or the gas barrier coating layer 22, the gas barrier adhesive can fill in the cracks and fill them, so that the deterioration of the gas barrier properties of the laminate 100 can be suppressed.
[0080] Gas barrier adhesives are adhesives that can exhibit gas barrier properties after curing. Examples of gas barrier adhesives include epoxy adhesives and polyester / polyurethane adhesives. Specific examples of gas barrier adhesives include "Maxive" manufactured by Mitsubishi Gas Chemical Company, Inc. and "Paslim" manufactured by DIC Corporation.
[0081] The oxygen permeability of the gas barrier adhesive is, for example, 150 cc / m 2 ·day·atm or less is preferable, and 100cc / m 2 ·day·atm or less is more preferable, and 80cc / m 2 ·day·atm or less is more preferable, and 50cc / m 2 By having the oxygen permeability within the above range, the gas barrier properties of the laminate 100 can be sufficiently improved.
[0082] The adhesive layer 30 can be formed by, for example, applying an adhesive by a bar coating method, a dipping method, a roll coating method, a gravure coating method, a reverse coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, a gravure offset method, or the like to form a coating film, and then drying and curing the coating film. From the viewpoint of suppressing cracking of the inorganic oxide layer 21, the adhesive layer 30 is preferably formed directly on the surface of the inorganic oxide layer 21 or the gas barrier coating layer 22. That is, the adhesive layer 30 is preferably formed by applying an adhesive directly on the surface of the inorganic oxide layer 21 or the gas barrier coating layer 22, and drying and curing it.
[0083] The temperature for drying the coating film may be, for example, 30 to 200° C., and preferably 50 to 180° C. The temperature for curing the coating film may be, for example, 20 to 70° C., and preferably 30 to 60° C. By keeping the drying and curing temperatures within the above ranges, the occurrence of cracks in the inorganic oxide layer 21 and the adhesive layer 30 can be suppressed, and the gas barrier property of the laminate 100 can be sufficiently improved.
[0084] The thickness of the adhesive layer 30 is preferably 0.1 to 20 μm, more preferably 0.5 to 10 μm, and even more preferably 1 to 5 μm. When the thickness of the adhesive layer 30 is 0.1 μm or more, it is possible to obtain a cushioning property that absorbs external impacts, which makes it easier to suppress cracking of the inorganic oxide layer 21 and further improves the gas barrier property of the laminate 100. When the thickness of the adhesive layer is 20 μm or less, it is likely that the flexibility of the laminate 100 can be sufficiently maintained.
[0085] The thickness of the adhesive layer 30 is preferably 50 times or more the thickness of the inorganic oxide layer 21. By making the thickness of the adhesive layer 30 50 times or more the thickness of the inorganic oxide layer 21, it is possible to obtain a cushioning property that absorbs external impacts, so that it becomes easier to suppress cracking of the inorganic oxide layer 21, and the gas barrier property of the laminate 100 can be further improved. The thickness of the adhesive layer 30 is preferably 300 times or less the thickness of the inorganic oxide layer 21. By making the thickness of the adhesive layer 30 300 times or less the thickness of the inorganic oxide layer 21, the flexibility and processability of the laminate 100 are excellent, and the cost can be reduced.
[0086] <Sealant layer> The sealant layer 40 is, for example, a layer made of a polyethylene resin. The sealant layer 40 is a layer that is bonded by heat fusion (heat sealing) when the laminate 100 is used to form a packaging material such as a packaging bag. The polyethylene resin constituting the sealant layer 40 may be a low-density polyethylene resin (LDPE), a linear low-density polyethylene resin (LLDPE), or a very low-density polyethylene resin (VLDPE) from the viewpoint of excellent heat sealability. From the viewpoint of environmental load, the sealant layer 40 may be made of a polyethylene resin derived from biomass or a recycled polyethylene resin. The sealant layer 40 may be, for example, made of a non-oriented polyethylene film.
[0087] Low density polyethylene has a density of 0.900 g / cm 3 More than 0.925g / cm 3 For linear low density polyethylene, polyethylene having a density of 0.900 g / cm3 or less can be used. 3 More than 0.925g / cm 3 For ultra-low density polyethylene, polyethylene with a density of 0.900 g / cm3 can be used. 3 Less than 100 mm of polyethylene can be used.
[0088] The sealant layer 40 may contain a resin other than polyethylene resin. Examples of resins other than polyethylene resin include olefin-based resins such as ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, and polybutene. The sealant layer 40 may contain additives such as antioxidants, lubricants, antiblocking agents, and antistatic agents.
[0089] The thickness of the sealant layer 40 may be, for example, 20 μm or more, 40 μm or more, or 50 μm or more. When the thickness of the sealant layer 40 is 20 μm or more, sufficient heat seal strength can be achieved. The thickness of the sealant layer 40 may be, for example, 200 μm or less, 170 μm or less, or 150 μm or less. When the thickness of the sealant layer 40 is 200 μm or less, excellent processability is achieved.
[0090] <Print layer> The laminate 100 may further include a printed layer (not shown). The printed layer is provided at a position visible from the outside of the laminate 100 for the purpose of displaying information about the contents, identifying the contents, or improving the design of the packaging bag. The printed layer may be provided, for example, on the surface of the outer layer 11 of the laminate 100, on the surface of the inorganic oxide layer 21, on the surface of the gas barrier coating layer 22, or on the surface of the sealant layer 40.
[0091] The method for forming the printed layer is not particularly limited, and known printing methods and printing inks can be used. The printing method and printing ink are appropriately selected in consideration of, for example, printability for each layer of the laminate 100, design such as color tone, adhesion, and safety as a food container.
[0092] Examples of printing methods include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among these, gravure printing is preferred from the viewpoints of productivity and high definition of the image.
[0093] In order to improve the adhesion of the printed layer, the surface of the layer forming the printed layer may be subjected to pretreatment such as corona treatment, plasma treatment, frame treatment, etc., or a coating layer such as an easy-adhesion layer may be provided.
[0094] <Packaging materials> The laminate 100 can be used as a packaging material for forming packaging bags, etc. Specifically, it can be used as a packaging material for flat bags, three-sided bags, palm-shaped bags, gusseted bags, standing pouches, pouches with spouts, pouches with beaks, etc.
[0095] The laminate 100 can be used as a packaging material as well as a film for electronic devices, a film for solar cells, a film for fuel cells, a substrate film, and the like. EXAMPLES
[0096] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0097] <Preparation of materials for making base film> The materials used for the preparation of the substrate film were PP (polypropylene), PA (polyamide), PBT (polybutylene terephthalate), EVOH (ethylene vinyl alcohol copolymer), PE (polyethylene), and A-PE (polyethylene: adhesive resin). Details of the materials used are summarized in Table 1.
[0098] [Table 1]
[0099] <Preparation of base film> The resins shown in Tables 2 to 5 constituting the surface layer, optional adhesive resin layer, intermediate layer, and back layer were respectively fed into a five-layer co-extruder, melt-kneaded at 190 to 230°C, and then fabricated into substrate films by air-cooled inflation. Substrate films having four or fewer layers were produced by feeding the same resin into two or more extruders. The polyethylene resin content of the substrate films fabricated in each example was 90% by mass or more. In addition, no stretching treatment was performed on any of the substrate films.
[0100] For the surface layer "PE(A)+PP" in Example 5, a material in which both were mixed in a mass ratio of PE(A):PP = 90:10 was used. In Example 5, which does not require an adhesive resin, PE(A) was fed into the extruder 2 as a constituent material for the intermediate layer. In Comparative Examples 1, 4 and 5, the tables formally indicate a surface layer, an intermediate layer and a back layer, but in all cases, there was no such concept and the substrate film was produced as a laminate having substantially a two-layer structure.
[0101] <Tip drop temperature> The probe drop temperature (softening point) of each layer of the substrate film was measured using an atomic force microscope equipped with a nanothermal microscope consisting of a cantilever (probe) with a heating mechanism. First, the substrate film was embedded in a visible light curing resin to obtain a measurement sample, and then, in a −140° C. environment, the measurement sample was cross-sectioned in a direction parallel to the TD direction using a diamond knife of a cryo-ultramicrotome.
[0102] After performing shape measurement of a 10 μm field of view on the measurement sample that had been cut in cross section in AC mode, the cantilever (probe) was separated from the sample by 5 to 10 μm in the Z direction. In this state, the detrend correction function of the device was performed in contact mode under conditions of a maximum applied voltage of 6 V and a heating rate of 0.5 V / s to correct the change in the deflection of the cantilever (probe) due to the application of voltage. Then, in contact mode, the cantilever was brought into contact with the sample so that the change in deflection before and after contact between the cantilever and the sample was 0.2 V. While maintaining a constant deflection value, a voltage was applied to the cantilever at a maximum applied voltage of 6 V and a heating rate of 0.5 V / s to heat the sample. The change in Z displacement during this process was recorded, and the measurement was stopped when the Z displacement changed from increasing to decreasing and fell by 50 nm from the point of change. When the Z displacement did not drop by 50 nm from the change point and reached the maximum applied voltage, the maximum applied voltage during the detrend correction and measurement was increased by 0.5 V and the measurement was performed again. The applied voltage at which the recorded Z displacement was maximized was converted to temperature and used as the probe drop temperature. This measurement was performed at 10 points within a 10 μm field of view, and the average value was used. In order to convert the applied voltage to temperature, polycaprolactone (melting point 60°C), low-density polyethylene resin (112°C), polypropylene resin (166°C), and polyethylene terephthalate resin (255°C) were measured as calibration samples, and a calibration curve of applied voltage and temperature was created. Here, the melting point is the melting peak temperature measured by a differential scanning calorimeter (DSC) at a heating rate of 5°C / min. The measurement method was the same as that of the sample, but the maximum applied voltage during detrend correction and measurement was 3.5V for polycaprolactone, 5.5V for low-density polyethylene resin, 6.5V for polypropylene, and 7.8V for polyethylene terephthalate resin. The relationship between the applied voltage at which the Z displacement was maximum when each calibration sample was measured was approximated by a cubic function using the least squares method to create a calibration curve, and the applied voltage when the sample was measured was converted to temperature. Tables 2 to 5 show the probe drop temperatures for each layer of the base film.
[0103] <Preparation of Laminate> The surface of the back layer side of the substrate film prepared in each example was subjected to a corona treatment. Next, an anchor coat layer, an inorganic oxide layer, a gas barrier coating layer, an adhesive layer, and a sealant layer were formed in this order on the surface of the substrate film by the method described later, and the substrate film / anchor coat layer / inorganic oxide layer / gas barrier coating layer / adhesive layer / sealant layer were laminated in this order, and then aged at 40° C. for 4 days to obtain a laminate.
[0104] <Anchor coat layer> Acrylic polyol and tolylene diisocyanate were mixed so that the number of NCO groups of tolylene diisocyanate was equal to the number of OH groups of the acrylic polyol, and diluted with ethyl acetate so that the total solid content (total amount of acrylic polyol and tolylene diisocyanate) was 5 mass%. β-(3,4 epoxycyclohexyl)trimethoxysilane was added to the diluted mixture so that it was 5 mass parts per 100 mass parts of the total amount of acrylic polyol and tolylene diisocyanate, and these were mixed to prepare a composition for forming an anchor coat layer (anchor coat agent). The anchor coat layer was formed by applying the composition for forming the anchor coat layer to the surface of the corona-treated base film by gravure coating and drying. The coating amount of the polyester resin in the anchor coat layer was 0.1 g / m 2 The thickness of the anchor coat layer was 0.1 μm.
[0105] <Inorganic oxide layer> When the inorganic oxide was silicon oxide, a transparent inorganic oxide layer (silica vapor deposition film) made of silicon oxide and having a thickness of 30 nm was formed on the anchor coat layer using a vacuum deposition apparatus using an electron beam heating method. The O / Si ratio of the silica vapor deposition film was 1.8. When the inorganic oxide was aluminum oxide, a transparent inorganic oxide layer (alumina vapor deposition film) made of aluminum oxide with a thickness of 15 nm was formed on the anchor coat layer using a vacuum deposition apparatus using an electron beam heating method. The O / Al ratio of the alumina vapor deposition film was 1.5.
[0106] <Gas barrier coating layer> A gas barrier coating agent was prepared by mixing the following liquids A, B, and C in a mass ratio of 70 / 20 / 10, respectively. The gas barrier coating agent was applied onto the inorganic oxide layer by gravure coating and dried to form a gas barrier coating layer with a thickness of 0.3 μm. Liquid A: A hydrolysis solution with a solid content of 5 mass% (SiO2 equivalent) obtained by mixing 17.9 g of tetraethoxysilane (Si(OC2H5)4), 10 g of methanol, and 72.1 g of 0.1N hydrochloric acid and stirring for 30 minutes. Liquid B: A mixed solution of 5% by mass of polyvinyl alcohol, water, and methanol in a mass ratio of 95:5 (water:methanol). Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixed solution of water / isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.
[0107] <Adhesive layer> The substrate film (gas barrier coating layer) and the sealant layer were bonded together by dry lamination using the following urethane adhesive or gas barrier epoxy adhesive. The thickness of the adhesive layer after drying was 3 μm. (Urethane adhesive) A urethane adhesive was obtained by mixing 100 parts by mass of Takelac A525 (manufactured by Mitsui Chemicals), 11 parts by mass of Takenate A52 (manufactured by Mitsui Chemicals), and 84 parts by mass of ethyl acetate.
[0108] (Epoxy adhesive: gas barrier adhesive) An epoxy-based adhesive was obtained by mixing 23 parts by mass of a solvent made by mixing ethyl acetate and methanol in a mass ratio of 1:1 with 16 parts by mass of Maxieve C93T (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 5 parts by mass of Maxieve M-100 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0109] <Sealant layer> The following films were used as the sealant layers: S-PE(A): Non-oriented film made of linear low-density polyethylene resin (LLDPE) (manufactured by Mitsui Chemicals Tocello, product name: TUX-MCS). S-PE(B): Non-oriented film made of linear low-density polyethylene resin (LLDPE) (manufactured by Mitsui Chemicals Tocello, product name: TUX HC). S-PE(C): Non-oriented film made of linear low-density polyethylene resin (LLDPE) (manufactured by Mitsui Chemicals Tocello, product name: TUX TC-S). S-PE(D): Non-oriented film made of linear low-density polyethylene resin (LLDPE) (manufactured by Mitsui Chemicals Tocello, product name: TUX VCS).
[0110] [evaluation] The laminates obtained in each example were evaluated for the following items. The results are shown in Tables 6 to 9.
[0111] <Recyclability> The content (mass%) of polyethylene resin in the laminate obtained in each example was calculated based on the following formula. All laminates were rated A (polyethylene resin content of 90 mass% or more). {(Mass of polyethylene resin in base film + mass of sealant layer) / mass of entire laminate} x 100
[0112] <Heat seal start temperature> The difference (T1-T2) between the heat seal initiation temperature T1 when the surface layers of the laminates obtained in each example were placed facing each other and heat sealed, and the heat seal initiation temperature T2 when the sealant layers were placed facing each other and heat sealed, was measured. Specifically, the surface layers of the laminate or the sealant layers were sandwiched between PET films in a state of facing each other, and heat-sealed using a heat sealer manufactured by Tester Sangyo Co., Ltd. under the conditions of a sealing pressure of 0.2 MPa, a sealing time of 1 second, and a sealing width of 10 mm. The sealing temperature was adjusted in 10°C increments between 90 and 240°C. The heat-sealed portions heat-sealed at each temperature were cut into 15 mm wide x 80 mm pieces, and a tensile tester manufactured by Shimadzu Corporation was used to perform T-shaped peeling at a tensile speed of 300 m / min to measure the heat-seal strength of the heat-sealed portions. The temperature at which the heat-seal strength reached 2 N / 15 mm or more was taken as the heat-seal rise temperature.
[0113] <Heat sealability> The laminate obtained in each example was cut into a 10 cm square, folded in half so that the sealant layer was on the inside, and heat-sealed using a heat seal tester under conditions of a pressure of 0.2 MPa and a heating time of 1 second. Then, (1) the heat-sealing temperature range of the laminate (maximum temperature at which the laminate can be heat-sealed - minimum temperature at which the laminate can be heat-sealed) was confirmed. In addition, (2) the heat-sealed parts of the obtained samples were visually observed to confirm the presence or absence of wrinkles in the heat-sealed parts. Evaluation was performed based on the following criteria. (1) Heat seal temperature range of laminates A: Above 20℃. B: Above 0℃ and below 20℃. (2) Good appearance of heat-sealed parts A: No wrinkles are observed in the heat sealed area. B: Wrinkles are observed in the heat-sealed area to a degree that the product can be used. C: Wrinkles were observed in the heat-sealed area to the extent that the product could not be used.
[0114] <Barrier processing suitability (processing stability)> The substrate film after the gas barrier layer was formed was visually inspected, and the barrier processing suitability was evaluated based on the following evaluation criteria. A: No wrinkles were observed in the appearance or rolled state of the base film. B: Slight wrinkles were observed in either the appearance or rolled state of the base film, but were still usable as a base film. C: Many wrinkles were observed in either the appearance or rolled state of the base film.
[0115] <Gas barrier properties> The laminate obtained in each example was measured for oxygen permeability (cm) in an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name OXTRAN-2 / 20, manufactured by MOCON) in accordance with JIS K 7126-2. 3 / (m 2 ·day·atm) was measured.
[0116] <Gas barrier properties after boiling treatment> The laminate obtained in each example was cut into two pieces measuring 15 cm x 10 cm, and the two cut-out laminates were stacked so that the sealant layers faced each other, and three sides were impulse sealed to form a pouch. 150 ml of water was placed in the pouch as the contents, and the remaining side was impulse sealed to produce a pouch (packaging bag) with four sides sealed. The produced pouch was boiled at 95°C for 30 minutes in a boiling treatment device. After the boiling treatment, the pouch was opened to remove the contents, thoroughly dried, and the oxygen permeability of the pouch after the boiling treatment was measured by the method described above.
[0117] <Adhesion> A 15 mm wide rectangular test piece was cut out from the laminate obtained in each example, and the laminate strength between the base film and the sealant layer was measured using a Tensilon universal testing machine RTC-1250 manufactured by Orientec Co., Ltd. in accordance with JIS Z 1707. The measurement was performed using a T-type peel at a peel speed of 300 mm / min.
[0118] [Table 2]
[0119] [Table 3]
[0120] [Table 4]
[0121] [Table 5]
[0122] [Table 6]
[0123] [Table 7]
[0124] [Table 8]
[0125] [Table 9] [Explanation of symbols]
[0126] Reference Signs List: 10, 50, 60... base film; 11, 51, 61... surface layer; 12, 52, 62... intermediate layer; 13, 53, 63... back layer; 20... gas barrier layer; 21... inorganic oxide layer; 22... gas barrier coating layer; 30... adhesive layer; 40... sealant layer; 100, 200, 300... laminate.
Claims
1. A laminate comprising a base film, an inorganic oxide layer, an adhesive layer, and a sealant layer in this order, the base film has a surface layer, an intermediate layer, and a back layer on a sealant layer side in this order; The surface layer contains a resin having a higher melting point than polyethylene resin, the intermediate layer contains polyethylene resin, and the back layer has a melting point of 0.926 g / cm 3 A polyethylene resin having a density of at least The probe drop temperature of the back layer is 130° C. or more and less than 150° C., and the probe drop temperature of the intermediate layer is higher than the probe drop temperature of the back layer; the sealant layer comprises a polyethylene resin; A laminate, wherein the content of the polyethylene resin in the laminate is 90 mass% or more based on the total amount of the laminate.
2. The laminate according to claim 1 , wherein the surface layer has a thickness of 0.3 μm or more and 6 μm or less.
3. The laminate according to claim 1 , wherein the intermediate layer has a probe drop temperature of 140° C. or higher.
4. The laminate according to claim 1 , wherein the thickness of the intermediate layer is 33% or more of the thickness of the base film.
5. The laminate according to claim 1 , wherein the substrate film is a non-oriented film.
6. The laminate according to claim 1 , further comprising a gas barrier coating layer on a surface of the inorganic oxide layer on the side of the sealant layer.
7. The laminate of claim 1 , wherein the adhesive layer comprises a gas barrier adhesive.
8. The laminate according to claim 1, wherein a difference (T1-T2) between a heat seal initiation temperature T1 when the surface layers are placed opposite each other and heat sealed and a heat seal initiation temperature T2 when the sealant layers are placed opposite each other and heat sealed is 40°C or more. <Method for measuring heat seal rise temperature> The surface layers or sealant layers of the laminate are sandwiched between PET films with each layer facing each other, and heat sealed using a heat sealer under the following conditions: sealing pressure 0.2 MPa, sealing time 1 second, and seal width 10 mm. The sealing temperature is adjusted in 10°C increments between 90 and 240°C. The heat-sealed portions heat-sealed at each temperature are cut out to a width of 15 mm, and T-peeled at a pulling speed of 300 m / min to measure the heat-seal strength of the heat-sealed portions. The temperature at which the heat-seal strength reaches 2 N / 15 mm or more is taken as the heat-seal rise temperature.
9. A packaging material comprising the laminate according to any one of claims 1 to 8.
Citation Information
Patent Citations
Aluminum vapor deposited polyethylene film and method of manufacturing the same
JP2001179878A
Film, laminate film and package composed of laminate film
JP2018024213A
Laminate, packaging material, packaging bag and stand pouch
JP2020055157A
